2020
DOI: 10.1161/circulationaha.119.044408
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody Signature in Cardiac Arrest

Abstract: Background: Cardiac arrest is a tragic event that causes 1 death roughly every 90 seconds worldwide. Survivors generally undergo a workup to identify the cause of arrest. However, 5% to 10% of cardiac arrests remain unexplained. Because cardiac arrhythmias underlie most cardiac arrests and increasing evidence strongly supports the involvement of autoantibodies in arrhythmogenesis, a large-panel autoantibody screening was performed in patients with cardiac arrest. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The study published in the present issue of Circulation 8 provides new insights in the field. The authors should be congratulated for their approach of real translational science from the clinic to the bench.…”
Section: Atrial Fibrillation and Autoimmunitymentioning
confidence: 88%
See 1 more Smart Citation
“…The study published in the present issue of Circulation 8 provides new insights in the field. The authors should be congratulated for their approach of real translational science from the clinic to the bench.…”
Section: Atrial Fibrillation and Autoimmunitymentioning
confidence: 88%
“…Main reinforcement loops known in the pathophysiology of atrial fibrillation (blue). Contribution of the new work proposed by Maguy et al 8 (red) and new questions raised by it (green). *Risk factors for atrial fibrillation (AF) include (nonexhaustively) aging, hypertension, diabetes, obesity, structural heat disease, and heart failure.…”
Section: Atrial Fibrillation and Autoimmunitymentioning
confidence: 96%
“…Antibodies (Abs) produced by the adaptive immunity that bind to self‐antigens are autoantibodies (AAbs). Production of AAbs can be accompanied by disease progression, such as autoimmune diseases, cancer, diabetes, and cardiovascular disease [1–4]. As such, AAbs have great value in understanding autoimmunity as well as clinical applications [5–9].…”
Section: Textmentioning
confidence: 99%
“…For example, patients with idiopathic cardiac arrest produce an AAb against the pore domain of the L-type voltage-gated calcium channel. Functional studies demonstrated that this AAb reduces the action potential duration of pluripotent stem cell-derived human cardiomyocytes through calcium channel inhibition, therefore acting as a proarrhythmogenic …”
Section: Introductionmentioning
confidence: 99%